Waste solution of acrylic-based emulsion with low solid content for cement concrete curing: a lab-scale study - Tran Anh Tu,; Nguyen Minh Khang,; Le Minh Son,; Nguyen Ngoc Tri Huynh,; Nguyen Khanh Son, (Vietnam Journal of Science and Technology, 2024)
In this study, we investigate using acrylic and acrylic-styrene emulsions as curing solution to enhance water resistance and prevent cracking in cement concrete surfaces. Our main objective is to investigate the possibilities of utilizing washing waste generated during the Rhomn & Haas factory - Dow Chemical Vietnam production process. This waste is currently being treated as solid even though it contains anywhere from 10-45% solid content. Through laboratory-scale experiments and analysis, we aim to assess the feasibility of employing this waste material as a cost-effective, technically sound, and environmentally sustainable solution for curing compound of concrete. The findings of this research have the potential to contribute to the advancement of eco-friendly waste management techniques while improving the durability and effectiveness of cement structures.